Pemberdayaan Masyarakat Melalui Inovasi Pengolahan Singkong Dalam Meningkatkan Perekonomian di Desa Rebalas Kecamatan Grati Kabupaten Pasuruan - Fajriyah, Alifatul; Meyta, Budiasi; Rofiqoh, Indarti (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
The development of technology and information is currently still not fully understood by the public, especially among the people of Rebalas Village. This shown by the lack of innovation residents of Rebalas Village regarding cassava food products which are abundant in their area. Cassava food products are generally only processed into monotonous products such as tape, jemblem, samiler and gethuk. So the people of Rebalas Village feel bored with the monotonous processing of cassava. However, when it’s processed into a variant of processed cassava properly, it will have a positive impact on becoming a product that is high quality, competitive and has economic value. The KKN work program that was initiated aims to increase the knowledge and understanding of the Rebalas Village community so that they have a high awareness of caring for the use of cassava. The implementation method is by (1) empowerment with processed cassava innovation activities, (2) counseling on the management of cassava into rainbowcakes and mockies (mocaf cookies), (3) training on making rainbowcake and mockies products, (4) counselling effective marketing methods to the village community Reply. This activity involved the Pendoso community, assisted by PKK women and KKN students. The results of this activity show an increase in the community's knowledge and interest in learning about utilizing cassava to make rainbowcakes and mockies which have high economic value and can help improve the economy of residents Rebalas Village.